Telessaúde na atenção primária: uma experiência do distrito sanitário Centro-Sul de Belo Horizonte - Edson Jose Carpintero Rezende (2011)
Society nowadays lives amongst several advances in Informatics field,counting with new resources that equip heathcare area and offer new modalities of service. Such innovations pressupose transmitting and keeping confidential information related to patients health. This review on the raccounts of literature intends on a reflection about confidentiality of information rendered by users of healthcare systems that use tele-health. Databases from Scielo and Lilacs were used in the search of published articles along the last 12 years, either in Portuguese, Spanish or English, and which somehow approached confidentiality issues in telehealth attendiments performed by healthcare services. In the process ofincorporating technological and communicational innovations in healthcare services, care is needed to deal with confidential information rendered, regading both ethical and legal issues, as well as using safety systems and also mechanisms in Informatics that make possible identifying people who were given access to such information